EFFECTIVENESS OF ADDITIONAL THERAPY OF MAHKOTA DEWA EXTRACT ON PAIN LEVELS OF OSTEOARTHRITIS PATIENTS - Purwaka, Barlaam Bagus Purwaka; Pinzon, Rizaldy Taslim; S, Sugianto (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Osteoarthritis is a form of arthritis that commonly occurs in the hands, hips and knees and affects the patient's level of pain. Osteoarthritis treatment currently uses conservative methods with NSAID therapy to reduce pain. However, long-term use has an impact on the digestive tract. Currently, traditional medicine is in great demand, such as the gods crown extract. The content of the gods crown extract can provide an alternative analgesic without side effects on the digestive tract. The purpose of this study was to measure the effectiveness of gods crown add-on therapy at the pain level of osteoarthritis patients at Bethesda Hospital, Yogyakarta. This study uses secondary data from the randomized clinical trial research design that has been conducted. The study was conducted within 2 weeks with 30 osteoarthritis patients as subjects at Bethesda Hospital, Yogyakarta. The instruments used were the Numerical Rating Scale and Subjective Global Assessment questionnaires. The results showed that there was a significant difference in the average pain level before and after therapy, both in the additional therapy group of Mahkota Dewa extract (p=0.001) and in the standard therapy group (Ibuprofen) (p=0.001). In addition, there was a significant difference in the average pain level where the additional crown of gods group had a larger average difference than the standard therapy (Ibuprofen) (p=0.013). This shows that the additional therapy of Mahkota Dewa extract is effective in reducing the level of pain which is greater in osteoarthritis patients at Bethesda Hospital Yogyakarta compared to the standard Ibuprofen therapy group.